Research of technological properties of Medicinal Plant raw material of Siberian Statice (Limonium gmelinii) - Kopel , Violeta; Barna , Oksana; Plaskonis , Yuliya (The Ukrainian Scientific Medical Youth Journal, 2022)
the article presents the results of studying the technological properties of medicinal plant raw materials Siberian Statice (Limonium gmelinii), namely specific, volumetric, bulk density, determination of absorption coefficient and swelling rate, as well as porosity, free volume layer and fractional composition. Grinded raw materials from the aboveground part of Siberian Statice, which included stems, inflorescences, flowers was the object of the study. Siberian Staticea (Limonium gmelinii) is a perennial herbaceous bare plant of the Kermek genus, which contains tannins, flavonoids, hydroxycinnamic acids, anthocyanins, coumarins, carbohydrates, polysaccharides, organic acids, amino acids and others. The raw material in the Genichesk district of the Kherson region was harvested in 2021. The study of basic technological properties was carried out according to generally accepted methods, which are listed in the State Pharmacopoeia of Ukraine. The data obtained during the study indicate that the composition of the grinded raw material is polydisperse and it is not possible to determine one predominant fraction. Particles with a size of 2,8-1,0 mm are about 80% of the composition. This diversity of composition can be explained by the fact that the studied aboveground part of plant raw materials includes a thick-branched stem, inflorescences with small regular flowers. The humidity of the studied raw materials is 0,23%. The specific density of raw materials is 1,3446 ± 0,0073 g/cm3, and the volumetric density of plant raw materials is 0,4679 ± 0,0450 g/cm3. Bulk mass after shrinkage decreased from 80 to 69, which is 13,75%. Volumetric shrinkage increased from 0,1251 g/cm3 to 0,1436 g/cm3. Indicators of porosity, porosity and free volume layer (0,6933 g/cm3, 0,7326 g/cm3, 0,9073 g/cm3, respectively) are quite high, which indicates a good absorption capacity of raw materials. The average value of the absorption coefficient was 6,33 ± 0,34, which indicates a high cost of extractant, and the swelling rate shows that the investigated raw material doesn’t swell, this indicates the presence of pores inside the stem, where the extractant is retained, but does not increase linear dimensions and volume plant raw materials. The technological properties of Siberian Statice (Limonium gmelinii) raw materials have been experimentally determined, which allow choosing the optimal extraction methods for the studied raw materials, namely the extraction method, the ratio of raw materials: extractant, the nature of the extractant.